2020
DOI: 10.1002/er.5962
|View full text |Cite
|
Sign up to set email alerts
|

A smart and transparent district heating mode based on industrial Internet of things

Abstract: Currently, both the heated building area and total pipe length have been increased significantly. Despite the rapid development of China's heating industry, the overall efficiency of district heating systems is relatively low. In this paper, an innovative smart and transparent heating mode is proposed to solve the problems of the current heating mode. The proposed method integrates two core technologies: the 3D-GIS digital twin model and the NB-IoT wireless communication system. The concept, main characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In complex real-time systems, decisions must be made quickly. It is necessary to develop automatic decision-making and control algorithms for the media and to restructure the media industry [19,20]. In addition, adopting a hierarchical structure and allowing some data to be processed by low-level programs will help data management.…”
Section: Results Analysismentioning
confidence: 99%
“…In complex real-time systems, decisions must be made quickly. It is necessary to develop automatic decision-making and control algorithms for the media and to restructure the media industry [19,20]. In addition, adopting a hierarchical structure and allowing some data to be processed by low-level programs will help data management.…”
Section: Results Analysismentioning
confidence: 99%
“…While the accurateness of the heat loads prediction is crucial to an efficient system as well as being able to continuously calibrate current systems. Echoing this, Liu et al [81] discussed how the implementation of a IoT wireless connection system enabled large amount of high quality data to be collected from the heat network and buildings to establish heating characteristics. This was then utilised to predict building loads which could then be used to determine what heating mode was most efficient.…”
Section: Controls and Communicationsmentioning
confidence: 99%
“…User controls integrating weather compensation for improved efficiencies and thermal comfort [26] Demonstrations of weather compensation of the whole heat network and more recent studies show that substation compensation which incorporates weather sensor, flow sensor, actuating valve, differential pressure controller to ensure appropriate operating conditions for the control valve [72,76] 5GDH controls to be provided with computational intelligence which is close to the human brain with the ability to optimise the DH network's performance; while the control system itself is split into three parts: dispatching and management, online energy consumption analysis, and accident alarm systems [78] DH networks in Tannheim using a fuzzy direct matrix control (DMC) to handle the inherent nonlinearity characteristics of DH by considering the volume flow rate at the plant as fuzzy variable; while the fuzzy DMC identified that the DH network was trading off between pumping and heat losses significantly impacting on the operational costs, and ultimately the overall efficiency of the network [79] IoT technology such as a temperature sensor installed in a heat exchanger, which can exploit the data to determine a buildings energy profile [80] Implementation of a IoT wireless connection system enables large amount of high-quality data to be collected from the heat network and buildings to establish heating characteristics to accurately predict building thermal loads [81] Easy access for customers to the DHS information, dynamic pricing and ability of the users to adopt to their desired habits/schedules are among objectives to be accomplished.…”
Section: Controls and Communications Focal Points Referencesmentioning
confidence: 99%